Improving outcomes and antibiotic stewardship (IOAS) for patients with Gram-positive bloodstream infections through use of rapid testing: a quasi-experimental multicentre study of the Accelerate PhenoTest™ BC Kit. (22nd May 2021) - MacVane, Shawn H.; Bhalodi, Amira A.; Dare, Ryan K.; Rosenbaum, Eric R.; Wolfe, Kaleb; Ford, Bradley; Ince, Dilek; Kinn, Patrick; Percival, Kelly M.; Humphries, Romney M.
Abstract: Background: Data from the Improving Outcomes and Antibiotic Stewardship for Patients with Bloodstream Infections: Accelerate PhenoTest™ BC Kit (AXDX) Registry Study were analysed to determine the impact of rapid organism identification and antimicrobial susceptibility testing (AST) for Gram-positive bacteraemia. Patients and methods: This multicentre, quasi-experimental study evaluated clinical and antimicrobial stewardship metrics following the implementation of AXDX. Data from hospitalized patients with bacteraemia were compared between groups, one that underwent testing on AXDX (post-AXDX) and one that underwent traditional identification and AST (pre-AXDX). An analysis of patients with Gram-positive bacteraemia was performed. The primary outcome was time to optimal therapy (TTOT). Secondary outcomes included time to first antibiotic modification (overall and Gram-positive), duration of unnecessary MRSA coverage, incidence of adverse events, length of stay and mortality. Results: A total of 219 (109 pre-AXDX, 110 post-AXDX) patients with Gram-positive bacteraemia were included. Median TTOT was 36.3 h (IQR, 16.9–56.7) in the pre-AXDX group and 20.4 h (IQR, 7.5–36.7) in the post-AXDX group ( P =  0.01). Compared with pre-AXDX, median time to first antibiotic modification (29.1 versus 15.9 h; P =  0.002), time to first Gram-positive antibiotic modification (33.2 versus 17.2 h; P =  0.003) and median duration of unnecessary MRSA coverage (58.4 versus 29.7 h; P =  0.04) were reduced post-AXDX. A trend towards decreased acute kidney injury (24% versus 13%; P =  0.06) was observed in the post-AXDX group. Groups did not differ in other secondary outcomes. Conclusions: Implementation of AXDX testing for patients with Gram-positive bacteraemia shortened the TTOT and reduced unnecessary antibiotic exposure due to faster antibiotic modifications.